Scaffolds from alternating block polyurethanes of poly(ɛ‐caprolactone) and poly(ethylene glycol) with stimulation and guidance of nerve growth and better nerve repair than autograft. Issue 7 (1st December 2014) - Niu, Yuqing; Li, Linjing; Chen, Kevin C.; Chen, Feiran; Liu, Xiangyu; Ye, Jianfu; Li, Wei; Xu, Kaitian
Abstract: Nerve repair scaffolds from novel alternating block polyurethanes (PUCL‐ alt ‐PEG) based on PCL and PEG without additional growth factors or proteins were prepared by a particle leaching method. The scaffolds have pore size 10−20 µm and porosity 92%. Mechanical tests showed that the polyurethane scaffolds have maximum loads of 5.97 ± 0.35 N and maximal stresses of 8.84 ± 0.5 MPa. Histocompatiblity of the nerve repair scaffolds was tested in a SD rat model for peripheral nerve defect treatment. Two types of treatments including PUCL‐ alt ‐PEG scaffolds and autografts were compared in rat model. After 32 weeks, bridging of a 12 mm defect gap by the regenerated nerve was observed in all rats. The nerve regeneration was systematically characterized by sciatic function index (SFI), electrophysiology, histological assessment including HE staining, immunohistochemistry, ammonia sliver staining, Masson's trichrome staining and TEM observation. Results revealed that nerve repair scaffolds from PUCL‐ alt ‐PEG exhibit better regeneration effects compared to autografts. Electrophysiological recovery was seen in 90% and 87% of rats in PUCL‐ alt ‐PEG and autograft groups respectively. Biodegradation in vitro and in vivo shows good degradation match of PUCL‐ alt ‐PEG scaffolds with nerve regeneration. It demonstrates that plain nerve repair scaffolds from PUCL‐ alt ‐PEG biomaterials can achieve peripheral nerve regeneration satisfactorily. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103: 2355–2364, 2015.